Pentingnya Perencanaan dalam Melakukan Aktifitas untuk Mendukung Produktifitas Individu Dewasa dengan ADHD - Santoso, Tri Budi (Jurnal Terapi Wicara dan Bahasa, 2024)
Abstract Background: ADHD conditions cause adult individuals to experience various difficulties in carrying out daily activities, both when working and carrying out activities on campus. Objectives: This study explores the benefits of activity planning to support the productivity of adult individuals diagnosed with ADHD. Methods: This qualitative research using the phenomenological method involved eight adult individual participants with ADHD. We collected data through interviews and observations. We used thematic analysis to analyze the collected data. Results: Two themes emerged from the thematic data analysis. The first theme, "Productivity of Adult Individuals with ADHD," comprises two sub-themes: the quality of productivity among adult individuals with ADHD and the productivity disorders they experience. The second theme underscores the significance of activity planning in boosting the productivity of adult individuals with ADHD, encompassing two sub-themes: the creation of a list of tasks and the advantages of activity planning for productivity. Conclusion: Adult individuals with ADHD experience difficulties when performing tasks at work and in academic activities.  Activity planning makes it easier for adults with ADHD to carry out daily work and activities. Keywords: ADHD, Planning activities